Method for producing stainless steel, method for lightweight treatment, stainless steel, and aqueous composition

By lightening the stainless steel with an aqueous composition, the problem of difficulty in realizing the lightweight and low density of stainless steel in the prior art is solved, and stainless steel with a density less than 7.4 g/cm3 is achieved, and thickness and durability are maintained.

CN119855943APending Publication Date: 2025-04-18MITSUBISHI GAS CHEM CO INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380065196.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-15
Filing Date
2023-09-14
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to achieve lightweight and low density of stainless steel by simple methods, especially in maintaining thickness and durability.

Method used

The stainless steel is lightened by an aqueous composition, which contains 0.1 to 5 mass % hydrogen peroxide, 1 to 30 mass % halide ions and 0 to 40 mass % copper ions. These components are in contact with the surface of the stainless steel to form fine recesses to achieve light weight.

Benefits of technology

The lightweight and low density of stainless steel are achieved, with a density less than 7.4 g/cm3, and without reducing the thickness, the generation of pinholes and deterioration of surface properties are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005305730000000141
    Figure BDA0005305730000000141
Patent Text Reader

Abstract

The present invention provides a low-density stainless steel, a method for producing the same, a method for reducing the weight of the stainless steel, an aqueous composition useful for reducing the weight of the stainless steel, and the like. The above-mentioned problem is solved by a method for manufacturing stainless steel, which comprises a lightening treatment step for lightening stainless steel using an aqueous composition, wherein the density of the lightened stainless steel is less than 7.4 g / cm3, and the like. According to the present invention, the weight and density of stainless steel can be reduced by a simple method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing stainless steel, a method for lightweighting stainless steel, stainless steel and an aqueous composition, and in particular to low-density stainless steel, a method for producing the same, a method for lightweighting stainless steel and an aqueous composition useful for lightweighting stainless steel. Background Art

[0002] Stainless steel has been studied in recent years for its excellent durability and weather resistance in various fields. For example, stainless steel is increasingly being used in electronic parts, battery collector foils, and automobile parts housings.

[0003] When stainless steel is used in various products, it is known that treatment for increasing the surface area (for example, Patent Document 1) or treatment for forming irregularities on the surface of the stainless steel (for example, Patent Document 2) is performed.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2011-168017

[0007] Patent Document 2: Japanese Patent Application Publication No. 2015-183239 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] Stainless steel is expected to be lightweight depending on its application, and stainless steel with a specified thickness and low density is sometimes required. It is also difficult to obtain stainless steel that achieves the specified lightweight and low density through conventional stainless steel manufacturing methods or surface treatment methods.

[0010] Solutions for solving problems

[0011] The present invention provides the following method for producing stainless steel, method for weight reduction, stainless steel, aqueous composition, etc.

[0012] That is, the present invention includes the following contents.

[0013] [1] A method for producing stainless steel, comprising a lightweighting step of lightweighting the stainless steel using an aqueous composition,

[0014] The density of the lightweight stainless steel is less than 7.4 g / cm 3 .

[0015] [2] The method for producing stainless steel according to [1] above, wherein the density of the lightweight stainless steel is 7.0 g / cm 3 the following.

[0016] [3] The method for producing stainless steel according to [1] or [2], wherein the density (g / cm 3 ) is the density of the stainless steel before lightweighting (g / cm 3 ) is less than 0.95 times.

[0017] [4] The method for producing stainless steel according to any one of [1] to [3] above, wherein the thickness of the lightweight stainless steel is 100 μm or less.

[0018] [5] The method for producing stainless steel according to any one of [1] to [4] above, wherein the thickness (μm) of the stainless steel after the lightweighting treatment is at least 0.8 times the thickness (μm) of the stainless steel before the lightweighting treatment.

[0019] [6] The method for producing stainless steel according to any one of [1] to [5] above, wherein the aqueous composition contains 0.1 to 5 mass % of hydrogen peroxide, 1 to 30 mass % of halide ions, and 0 to 40 mass % of copper ions.

[0020] [7] A stainless steel having a density less than 7.4 g / cm 3 , thickness is less than 100μm.

[0021] [8] A method for lightweighting stainless steel, comprising a lightweighting step of lightweighting the stainless steel using an aqueous composition,

[0022] The density of the lightweight stainless steel is less than 7.4 g / cm 3 .

[0023] [9] An aqueous composition for reducing the weight of stainless steel, the aqueous composition comprising 0.1 to 5% by mass of hydrogen peroxide, 1 to 30% by mass of halide ions, and 0 to 40% by mass of copper ions.

[0024] Effects of the Invention

[0025] According to the present invention, it is possible to realize a method for producing stainless steel, a method for lightweighting treatment, an aqueous composition, and stainless steel having a low density, which enable the weight and density of stainless steel to be reduced by a simple method.

[0026] According to the present invention, it is preferred to achieve lightweighting without making foil-shaped or plate-shaped stainless steel so thin. In addition, according to the present invention, for example, stainless steel with low density and surface properties such as the generation of pinholes can be prevented from being deteriorated, and a method for making such stainless steel can be achieved. DETAILED DESCRIPTION

[0027] Hereinafter, the present invention will be described in detail, but the present invention is not limited to the following contents, and various modifications can be made without departing from the gist of the present invention.

[0028] [1. Method for manufacturing stainless steel]

[0029] The method for manufacturing stainless steel of the present invention includes a lightweighting treatment step of lightweighting stainless steel using an aqueous composition. According to the method for manufacturing stainless steel of the present invention, the thickness of stainless steel in a plate or foil shape before lightweighting can be substantially maintained while being lightweight and low-density.

[0030] (1-1. Properties of stainless steel)

[0031] The density of stainless steel after lightweight treatment is less than 7.4g / cm 3 (7.40g / cm 3 The density of the stainless steel according to one embodiment of the present invention, for example, the stainless steel obtained by weight reduction treatment, is preferably 7.3 g / cm 3 , 7.29g / cm 3 Below, less than 7.29g / cm 3 , 7.28g / cm 3 Below or 7.2g / cm 3 Below, more preferably 7.18 g / cm 3 Below, 7.15g / cm 3 Below, 7.1g / cm 3 or 7.0g / cm 3 Below, more preferably 6.9 g / cm 3 or 6.8g / cm 3 The lower limit of the density of the stainless steel after the weight reduction treatment varies depending on the application and is not particularly limited, but is generally preferably 1.3 g / cm from the perspective of durability and weather resistance. 3 above.

[0032] The density value D1 (g / cm 3 ) is preferably the density value D2 (g / cm2) of the stainless steel which is the same stainless steel and has not been subjected to lightweight treatment. 3 ), more preferably 0.93 times or 0.91 times, further preferably 0.90 times or 0.88 times, particularly preferably 0.85 times or 0.82 times or 0.80 times. The lower limit of the density ratio D1 / D2 before and after the lightweight treatment varies according to the application and is not particularly limited. From the perspective of durability and weather resistance, it is usually preferably 0.16 times or more.

[0033] The density value D1 (g / cm 3 ) is the same as the density value D2 (g / cm 3 ) difference, i.e. D2-D1(g / cm 3 ) is preferably 0.2 (g / cm 3 ) or more, more preferably 0.4 (g / cm 3 ) or more, 0.5(g / cm 3 ) or above or 0.6(g / cm 3 ) or more, more preferably 0.8 (g / cm 3 ) or more, 0.9(g / cm 3 ) or above or 1.0(g / cm 3 ) or more, particularly preferably 1.2 (g / cm 3 ) or more, 1.4(g / cm 3 ) or above or 1.6(g / cm 3 The density difference before and after the lightweight treatment is D2-D1 (g / cm 3 The upper limit of the viscosity varies depending on the application and is not particularly limited. From the perspective of durability and weather resistance, it is usually preferably 6.7 (g / cm 3 )the following.

[0034] The shape and thickness of the stainless steel to be subjected to the lightweight treatment are not particularly limited, and foil-shaped or plate-shaped stainless steel is preferably used. When foil-shaped stainless steel, i.e., stainless steel foil, is subjected to the lightweight treatment, the thickness is, for example, 100 μm or less, preferably 50 μm or less or 25 μm or less, more preferably 20 μm or less or 18 μm or less, further preferably 15 μm or less or 12 μm or less, and particularly preferably 10 μm or less. The lower limit of the thickness varies depending on the application and is not particularly limited, but is preferably 1 μm or more from the aspects of durability and weather resistance.

[0035] When plate-shaped stainless steel is subjected to lightweight treatment, the thickness is, for example, 2.0 mm or less, preferably 1.5 mm or less, more preferably 1.2 mm or less or less, further preferably 1.1 mm or less, less than 1.1 mm or 1.0 mm or less, and particularly preferably 0.8 mm or less. The lower limit of the thickness varies depending on the application and is not particularly limited, but is preferably 0.1 mm or more from the perspective of durability and weather resistance.

[0036] The thickness T1 (μm) of the stainless steel after the lightweight treatment is preferably 0.80 times or more (T1 / T2≥0.80) the thickness T2 (μm) of the stainless steel which is the same stainless steel and has not been lightweighted, more preferably 0.85 times or more or 0.90 times or more, further preferably 0.95 times or more or 0.98 times or more, and particularly preferably 1.0 times the thickness before the treatment.

[0037] (1-2. Types of stainless steel)

[0038] The type of stainless steel to be subjected to the weight reduction treatment using the aqueous composition of the present invention is not particularly limited, and examples thereof include the following stainless steels.

[0039] That is, chromium-nickel stainless steels specified by JIS G4305 standard, including SUS304, SUS316, SUS321, SUS347 and SUS329J1; ferritic stainless steels (chromium stainless steels) including SUS405, SUS430, SUS434, SUS444, SUS447 and SUSXM27; and precipitation hardening systems (chromium-nickel stainless steels) including SUS630, SUS631 and SUH660.

[0040] As the object of the weight reduction treatment by the aqueous composition, among the above-mentioned stainless steels, SUS304, SUS430 series (SUS430 and SUS430LX, etc.), SUS444, etc. are more preferable.

[0041] (1-3. Aqueous composition)

[0042] The aqueous composition used in the method for manufacturing stainless steel preferably contains 0.1 to 5% by mass of hydrogen peroxide, 1 to 30% by mass of halide ions, and 0 to 40% by mass of copper ions, based on the total amount of the aqueous composition. The details of the components of the aqueous composition will be described later. By forming fine recesses on the surface of the stainless steel with the aqueous composition, lightweighting can be achieved without significantly reducing the thickness of the stainless steel.

[0043] In the lightweight treatment method for lightweighting the surface of stainless steel of the present invention, a lightweight treatment step is performed. That is, the lightweight treatment method of the present invention includes a lightweight treatment step of lightweighting the surface of stainless steel using the above-mentioned aqueous composition. Here, lightweight treatment of the surface of stainless steel using an aqueous composition means that the aqueous composition used in the treatment is brought into contact with the surface of stainless steel. It can be seen from this that the lightweight treatment method for stainless steel of the present invention at least includes a step of bringing the aqueous composition into contact with the surface of stainless steel.

[0044] (1-4. Conditions for Lightweighting)

[0045] In the weight-reducing treatment step, the aqueous composition is brought into contact with stainless steel to be treated.

[0046] In the light-weighting treatment step, the light-weighting treatment temperature is preferably 20 to 60° C., more preferably 25 to 55° C., and particularly preferably 30 to 50° C. Thus, even at a lower temperature, for example, at room temperature of 25° C., the light-weighting treatment method for stainless steel of the present invention is excellent in this respect. Here, the light-weighting treatment temperature refers to the temperature when the aqueous composition is brought into contact with the stainless steel surface, and particularly refers to the liquid temperature of the aqueous composition in contact with the stainless steel surface.

[0047] In addition, in the lightweight treatment process, the lightweight treatment time is preferably 30 seconds to 120 seconds, more preferably 40 seconds to 100 seconds, and particularly preferably 50 seconds to 90 seconds. In this way, the stainless steel can be lightweighted even if it is not so long. In this regard, the lightweight treatment method of the stainless steel of the present invention is excellent. Here, the lightweight treatment time refers to the time when the aqueous composition is brought into contact with the surface of the stainless steel. For example, it is the time when the stainless steel is immersed in the aqueous composition, and the time from when the aqueous composition is sprayed on the surface of the stainless steel to when the aqueous composition is removed by water or the like.

[0048] The method of bringing the aqueous composition into contact with the surface of stainless steel is not particularly limited, and for example, a method of bringing the aqueous composition into contact with stainless steel by dripping or spraying (spray treatment) or a method of immersing stainless steel in the aqueous composition can be adopted. In the present invention, any method can be adopted. For example, there can be cited: a method of spraying an aqueous composition onto stainless steel processed into a specific shape to obtain lightweight stainless steel; a method of providing a dripping device, a spraying device or an immersion device for the aqueous composition between stainless steel foil rolls, and using a roll-to-roll method, while the stainless steel foil is unwound and moved from a roll formed by winding an untreated stainless steel foil, the aqueous composition is supplied to the vicinity of the above device, and the lightweight stainless steel foil is wound to obtain a roll, etc.

[0049] In addition, the stainless steel subjected to the weight reduction treatment in the weight reduction treatment step may be subjected to a treatment such as water washing (cleaning step).

[0050] [2. Lightweight treatment method for stainless steel]

[0051] The above-mentioned lightweight treatment process is not only useful as a part of the stainless steel manufacturing method, but also as a post-treatment of the stainless steel after manufacturing. The lightweight treatment method of the stainless steel of the present invention includes the above-mentioned lightweight treatment process. Therefore, in the lightweight treatment used in the lightweight treatment method, the properties and types of the stainless steel, the components of the aqueous composition, the conditions of the lightweight treatment, etc. are as described above.

[0052] [3. Aqueous composition]

[0053] The aqueous composition of the present invention is suitable for use in the above-mentioned method for manufacturing stainless steel or the method for lightweighting stainless steel. The aqueous composition of the present invention comprises 0.1 to 5% by mass of hydrogen peroxide, 1 to 30% by mass of halide ions, and 0 to 40% by mass of copper ions, based on the total amount of the aqueous composition. In addition to these components, the aqueous composition may further comprise water, in particular ion-exchanged water or ultrapure water.

[0054] Hereinafter, each component of the aqueous composition will be described.

[0055] (3-1. Hydrogen peroxide)

[0056] The hydrogen peroxide contained in the aqueous composition is usually mixed with other components in the form of an aqueous solution of appropriate concentration. The concentration of hydrogen peroxide in the aqueous hydrogen peroxide solution used in the preparation of the aqueous composition is not particularly limited, and may be, for example, 10% to 90%, preferably 35% to 60% according to industrial standards.

[0057] In addition, hydrogen peroxide may contain about 0.01 mass % or less of a stabilizer, and examples of permissible stabilizers include sulfuric acid, phosphoric acid, etc. The production process and acquisition route of hydrogen peroxide are not limited, and for example, hydrogen peroxide produced by the anthraquinone method may be used.

[0058] The concentration of hydrogen peroxide in the aqueous composition is 0.1 to 5.0% by mass, preferably 0.2 to 4.5% by mass, more preferably 0.3 to 4.5% by mass or 0.2 to 4.0% by mass, further preferably 0.35 to 3.0% by mass or 0.3 to 3.5% by mass, particularly preferably 0.4 to 2.0% by mass, 0.4 to 1.5% by mass, 0.45 to 1.2% by mass or 0.5 to 1.0% by mass, based on the total amount (total mass) of the aqueous composition.

[0059] In addition, the lower limit of the concentration of hydrogen peroxide in the aqueous composition may be, for example, 0.001 mass%, 0.01 mass%, 0.05 mass%, 0.15 mass%, 0.2 mass%, 0.25 mass%, 0.3 mass%, 0.35 mass%, 0.4 mass%, 0.45 mass%, or 0.5 mass%, based on the total amount (total mass) of the aqueous composition, and the upper limit of the concentration of hydrogen peroxide contained in the aqueous composition may be, for example, 4.8 mass%, 4.5 mass%, 4.2 mass%, 4.0 mass%, 3.8 mass%, 3.5 mass%, 3.2 mass%, 3.0 mass%, 2.8 mass%, 2.5 mass%, 2.2 mass%, 2.0 mass%, 1.8 mass%, 1.5 mass%, 1.2 mass%, 1.0 mass%, etc., based on the total amount (total mass) of the aqueous composition.

[0060] The concentration range of hydrogen peroxide can be selected from a range obtained by appropriately combining the above lower limit value and upper limit value.

[0061] By setting the concentration of hydrogen peroxide within the above range, the effects of the present invention tend to be more appropriately achieved, and even if copper ions, halide ions, etc. described later coexist in the aqueous composition, the possibility of heat generation or foaming associated with the decomposition of hydrogen peroxide can be suppressed, thereby ensuring work safety.

[0062] (3-2. Halide ions (halogen ions))

[0063] The type of halide ion contained in the aqueous composition is not particularly limited, and may be, for example, fluoride ion, chloride ion, bromide ion, or iodide ion. From the viewpoint of ease of handling and economic efficiency, chloride ion is more preferred.

[0064] The halogen compound providing halide ions is not particularly limited, and examples thereof include hydrochloric acid, alkali metal halides such as sodium halide and potassium halide, alkaline earth metal halides such as calcium halide, ammonium halide, copper halide, and hydrogen halide. Among them, hydrochloric acid, alkali metal halide or hydrogen halide is preferred, and hydrochloric acid or sodium chloride is more preferred, from the viewpoint of more effectively and reliably exerting the effects of the present invention.

[0065] The halogen compound can be used alone or in combination of two or more. It should be noted that the halogen compound can be repeated with the following copper compound. For example, when a copper halide is used as a source of halide ions, the copper halide is also equivalent to a copper compound as a source of copper ions. As the copper halide, copper chloride is preferred. It can be considered that the halogen compound (halide ion) causes pitting of the passivation film during the lightweight treatment of the stainless steel surface.

[0066] The concentration of halide ions in the aqueous composition is 1 to 30% by mass, preferably 2.0 to 25% by mass, more preferably 4.0 to 22% by mass or 3.0 to 20% by mass, and particularly preferably 5.0 to 15% by mass, 8 to 15% by mass or 10 to 15% by mass, based on the total amount (total mass) of the aqueous composition.

[0067] In addition, as the range of the concentration of halide ions in the aqueous composition, any one of 0.01 mass%, 0.1 mass%, 0.5 mass%, 1.0 mass%, 2.0 mass%, 3.0 mass%, 5.0 mass%, 8.0 mass%, 10.0 mass% and 12.0 mass% based on the total amount (total mass) of the aqueous composition is set as the lower limit, and any one of 29 mass%, 28 mass%, 27 mass%, 26 mass% and 25 mass% based on the total amount of the aqueous composition can be set as the upper limit.

[0068] The concentration range of the halide ions can be appropriately selected from a range obtained by appropriately combining the above lower limit value and upper limit value.

[0069] By setting the concentration of halide ions within the above range, there is a tendency that the effects of the present invention can be more appropriately achieved. More specifically, in an aqueous composition in which the concentration of halide ions is within the above range, the pitting reaction of stainless steel can be prevented from proceeding, fine recesses can be formed on the surface, and the decomposition reaction of hydrogen peroxide can be prevented to ensure safety.

[0070] (3-3. Copper ions)

[0071] The concentration of copper ions in the aqueous composition is 0 to 40% by mass based on the total amount (total mass) of the aqueous composition. That is, the aqueous composition of the present invention does not contain copper ions or the content of copper ions is 40% by mass or less based on the total amount (total mass) of the aqueous composition.

[0072] The copper ions in the aqueous composition can be generated by mixing a copper compound as a copper ion source with other components. The type of the copper ion source is not particularly limited as long as it is a copper compound that can supply copper ions to the aqueous composition.

[0073] For example, it can be an anhydrous substance or a pentahydrate, and copper sulfates such as copper sulfate (II), copper chlorides such as copper chloride (II), copper tetrafluoroborate, copper bromide (II), copper oxide (II), copper phosphates, copper acetates, copper formates, copper nitrates, etc. can be enumerated. Among them, from the viewpoint of more effectively and reliably playing the effect of the present invention, ease of operation, and economy, preferred copper sulfates or copper chlorides, more preferably copper sulfate (II) or copper chloride (II), further preferred copper sulfate (II). They can be used alone or in combination of more than two.

[0074] It is presumed that copper ions contained in the aqueous composition cause a substitution reaction with nickel and chromium, which are components of the stainless steel, during the weight reduction treatment, and that the substitution reaction products derived from the copper ions are then removed to form recessed portions on the surface.

[0075] In order to improve the quality of stainless steel after lightening treatment, and in particular, in the aqueous composition used for treating thin stainless steel foil, it is preferred to adjust the content of copper ions in order to prevent the generation of extremely thin areas and pinholes as described below.

[0076] The concentration of the copper ion contained in the aqueous composition is 40% by mass or less, preferably 25% by mass or less, 20% by mass or less or 15% by mass or less, more preferably 12% by mass or less or 10% by mass or less, or 7.0% by mass or less, 5.0% by mass or less or 3.0% by mass or less. As the preferred concentration range of copper ion, preferably 0 to 3.0% by mass, preferably 0 to 2.5% by mass, more preferably 0 to 1.5% by mass, further preferably 0.1 to 1.5% by mass, or 0.3 to 1.5% by mass or 0.5 to 1.5% by mass.

[0077] The lower limit of the concentration of copper ions in the aqueous composition is 0% by mass based on the total amount (total mass) of the aqueous composition, but may be, for example, 0.00001% by mass (0.1 ppm by mass), 0.0001% by mass (1 ppm by mass), 0.001% by mass, 0.01% by mass, 0.02% by mass, 0.03% by mass, 0.05% by mass, 0.07% by mass, or 0.1% by mass.

[0078] In addition, the upper limit of the copper ion concentration in the aqueous composition is based on the total amount of the aqueous composition, and may be, for example, 30 mass %, 25 mass %, 20 mass %, 17 mass %, 15 mass %, 10 mass %, 7.0 mass %, 5.0 mass %, 3.0 mass %, 2.5 mass %, 2.0 mass %, 1.8 mass %, etc.

[0079] The range of the copper ion concentration can be selected from a range obtained by appropriately combining the above lower limit value and upper limit value.

[0080] When the concentration of copper ions is within the above range, the effects of the present invention tend to be more appropriately achieved.

[0081] On the other hand, when the concentration of copper ions in the aqueous composition is too high, pinholes and extremely thin areas are easily generated in the stainless steel after the weight reduction treatment. When the concentration of copper ions is too low, there is a possibility that recesses cannot be formed on the surface and the weight reduction treatment cannot be performed efficiently.

[0082] (3-4. Additives contained in aqueous composition)

[0083] The aqueous composition of the present invention may further contain additives as components other than the above-mentioned hydrogen peroxide, copper ions and halide ions within the scope of exerting the effects of the present invention. As additives, for example, heterocyclic nitrogen compounds (azole compounds), organic solvents, etc. may be cited. These may be used alone or in combination of two or more. In addition, surfactants, pH adjusters, etc. may also be cited as additives, but these are preferably not included in the aqueous composition of the present invention.

[0084] The concentration of the additives that may be contained in the aqueous composition is preferably 10% by mass or less, more preferably 5.0% by mass or less, more preferably 2.0% by mass or less, and particularly preferably 1.0% by mass or less.

[0085] (3-5. Water)

[0086] The aqueous composition of the present invention may contain water, preferably water. The water is not particularly limited, but preferably water from which metal ions, organic impurities, particles, etc. are removed by distillation, ion exchange treatment, filter treatment, various adsorption treatments, etc., more preferably pure water, and particularly preferably ultrapure water.

[0087] The content of water in the aqueous composition of the present invention is the remainder of the above-mentioned components and additives described in detail later, and is not particularly limited. It is preferably 50 to 98% by mass, more preferably 60 to 95% by mass, further preferably 75 to 93% by mass, and particularly preferably 85 to 90% by mass, based on the total amount (total mass) of the aqueous composition.

[0088] The aqueous composition of the present invention is preferably a dissolving liquid, and preferably does not contain components that are insoluble in the composition as a dissolving liquid, for example, solid particles such as abrasive particles.

[0089] (3-6. Functions and properties of aqueous composition)

[0090] It is considered that the aqueous composition containing the above-mentioned components can efficiently form recessed portions on the surface of stainless steel as follows, thereby achieving weight reduction.

[0091] The halide ions play a role in pitting the oxide film usually formed on the surface of stainless steel. It is believed that, as mentioned above, the copper ions have a role in substitution reaction with nickel and chromium as stainless steel components, and then the substitution reaction products from the copper ions are removed to form a large concave portion on the surface of the stainless steel.

[0092] In addition, hydrogen peroxide plays a role in removing the substitution reaction product derived from copper ions after the above-mentioned substitution reaction.

[0093] Furthermore, by containing the aqueous composition with the content of copper ions adjusted to an appropriate range, it is possible to prevent the generation of extremely thin areas and pinholes in stainless steel, particularly stainless steel foil, after weight reduction treatment.

[0094] The aqueous composition of the present invention is prepared by adding the above-mentioned hydrogen peroxide-containing component, halide ion supplying component, water, and, if necessary, a copper ion supplying component and other components, and stirring until the mixture is uniform.

[0095] The properties of the aqueous composition are not particularly limited, but the pH is preferably -1.0 to 4.0, more preferably -0.5 to 3.0, further preferably -0.25 to 2.5, particularly preferably -0.1 to 2.0, 0.0 to 1.5, 0.005 to 1.0, or 0.01 to 0.5. The pH can be measured by the method described in Examples.

[0096] [4. Stainless steel]

[0097] The stainless steel of the present invention has a strength of less than 7.4 (g / cm 3 )(7.40g / cm 3 The density of the stainless steel according to one embodiment of the present invention, for example, the stainless steel obtained by lightweight treatment, is preferably 7.3 g / cm 3 , 7.29g / cm 3 Below, less than 7.29g / cm 3 , 7.28g / cm 3 Below or 7.2g / cm 3 Below, more preferably 7.18 g / cm 3 Below, 7.15g / cm 3 Below, 7.1g / cm 3 or 7.0g / cm 3 Below, more preferably 6.9 g / cm 3 or 6.8g / cm 3 the following.

[0098] Although it is difficult to produce such low-density stainless steel by conventional production methods and treatment methods, it can be easily produced by a production method and a lightweight treatment method including the above-mentioned lightweight treatment step. That is, according to the above-mentioned lightweight treatment step, lightweight stainless steel without a significant change in thickness can be obtained by substantially only one-stage treatment, that is, lightweight treatment by only contacting the aqueous composition of the present invention with the surface of the stainless steel to be treated, or only further appropriate cleaning (e.g., water cleaning) as needed.

[0099] Furthermore, as described above, the treatment conditions in the weight reduction treatment are mild and the time required is short, so that lightweight stainless steel can be obtained efficiently.

[0100] Such lightweight / low-density stainless steel can be used, for example, for battery collector foils such as solid-state batteries and lithium-ion batteries, solar cell substrates, flexible substrates for electronic devices, substrates for power storage devices, carriers for exhaust gas purification catalysts, etc., electromagnetic wave shielding components and heat dissipation components. The lightweight stainless steel foil obtained by the manufacturing method of stainless steel of the present invention is suitable for use as a battery collector foil, for example.

[0101] Example

[0102] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.

[0103] (thickness)

[0104] The thickness of the surface-treated stainless steel foils in Examples and Comparative Examples and the untreated stainless steel foils in Reference Examples 1 to 4 was measured using a digital micrometer (MDC-25MXT manufactured by Mitutoyo Corporation).

[0105] (density)

[0106] For the surface-treated stainless steel foils in Examples and Comparative Examples and the untreated stainless steel foils in Reference Examples 1 to 4, the density was calculated by the following formula (1) using the weight (D) of the stainless steel foil used, the area (S) of the stainless steel foil used, and the thickness (T) of the stainless steel foil measured as described above.

[0107]

[0108] (Checking the presence or absence of pinholes)

[0109] The surface-treated foils obtained in Examples and Comparative Examples were visually observed for their surface shapes. When no pinholes (fine through holes) were observed, the foils were evaluated as "good", and when pinholes were observed, the foils were evaluated as "bad".

[0110] [Example 1]

[0111] A stainless steel (foil) made of SUS444 having a thickness of 10 μm and a length of 30 mm×30 mm in the longitudinal and lateral directions was prepared (Reference Example 1).

[0112] An aqueous composition was prepared by adding hydrogen peroxide (1.7 g of a 60 wt% aqueous hydrogen peroxide solution) and 72 wt% (143 g) of a 35 wt% aqueous solution of hydrochloric acid to 55 ml of ultrapure water. - ) is 25% by mass based on the total amount of the aqueous composition.

[0113] The stainless steel foil was immersed in the aqueous composition at a liquid temperature of 30°C for 60 seconds. Then, the immersed stainless steel foil was thoroughly washed with ultrapure water and then fully dried to obtain a surface-treated foil. The surface-treated foil obtained was measured according to the above method, and the results showed that the thickness was 9 μm and the density was 6.6 g / cm 3 In addition, according to the above (Confirmation of the Presence of Pinholes), the surface shape was visually observed, and as a result, no pinholes (fine through holes) were confirmed, and the evaluation was "good".

[0114] [Examples 2 to 7 / Comparative Examples 1 to 4]

[0115] The stainless steel foil was subjected to weight reduction treatment in the same manner as in Example 1, except that any of the stainless steel to be treated, the properties of the aqueous composition, and the conditions of the weight reduction treatment method were changed as shown in Table 1 below, to obtain a surface-treated foil.

[0116] It should be noted that in Examples 4 and 7, copper ions (Cu 2+ ) were used as the supply source, 3.9 g and 12 g of copper sulfate pentahydrate (CuSO4·5H2O) were used respectively, and in Comparative Examples 2 and 3, 133 g and 133 g of iron (III) chloride hexahydrate (FeCl3·6H2O) were used respectively.

[0117] Table 1 shows the results of the thickness and density of the obtained surface-treated foil.

[0118] [Table 1]

[0119]

[0120] Industrial Applicability

[0121] In the above-mentioned each embodiment of the aqueous composition of specific composition, it is confirmed that stainless steel can be lightened efficiently with less process and short time, and there is no great change in the thickness of stainless steel before and after treatment. In addition, the stainless steel after treatment has a roughly uniform thickness, and no defects such as pinholes are found. When the stainless steel, particularly the stainless steel foil, which is low-densified in a good state of maintaining the appearance, is used for battery collector foil, automobile component housing, etc., dielectric substances and organic matter can be effectively attached or maintained. In addition, in the component for heat dissipation, lightweight and low-densified stainless steel can also be appropriately used.

[0122] Therefore, the present invention can be confirmed to have industrial applicability in the field of processing stainless steel as a material member, for example, a material member used in the above-mentioned products.

Claims

1. A method for producing stainless steel, comprising a lightweighting step of lightweighting the stainless steel using an aqueous composition, The density of the lightweight stainless steel is less than 7.4 g / cm 3 .

2. The method for producing stainless steel according to claim 1, wherein: The density of the lightweight stainless steel is 7.0 g / cm 3 the following.

3. The method for producing stainless steel according to claim 1, wherein: The density of the stainless steel after the lightweight treatment is less than 0.95 times the density of the stainless steel before the lightweight treatment, and the unit of the density of the stainless steel is g / cm 3 .

4. The method for producing stainless steel according to claim 1, wherein: The thickness of the lightweight stainless steel is 100 μm or less.

5. The method for producing stainless steel according to claim 1, wherein: The thickness of the stainless steel after the weight reduction treatment is at least 0.8 times the thickness of the stainless steel before the weight reduction treatment, and the unit of the thickness of the stainless steel is μm.

6. The method for producing stainless steel according to claim 1, wherein: The aqueous composition comprises 0.1 to 5 mass % of hydrogen peroxide, 1 to 30 mass % of halide ions, and 0 to 40 mass % of copper ions.

7. A stainless steel having a density less than 7.4 g / cm 3 , thickness is less than 100μm.

8. A method for lightweighting stainless steel, comprising a lightweighting step of lightweighting the stainless steel using an aqueous composition, The density of the lightweight stainless steel is less than 7.4 g / cm 3 .

9. An aqueous composition for reducing the weight of stainless steel, the aqueous composition comprising 0.1 to 5% by mass of hydrogen peroxide, 1 to 30% by mass of halide ions, and 0 to 40% by mass of copper ions.

Citation Information

Patent Citations

  • Composite in which stainless-steel plate and molding of thermoplastic resin composition are bonded, and method for manufacture thereof

    JP2011168017A

  • Surface processing method for stainless steel and heat exchanger using the same

    JP2015183239A